KEABSAHAN PERJANJIAN ASURANSI DALAM HUKUM KEPERDATAAN - Hery Yoga Sastrawan, I Gede; Tuni Cakabawa L., Putu (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014)
Coverage is an agreement by which committed them selves to the insured to receive a premium, to providere imbursement to him for the loss, damage or loss of expected benefits that maybe suffered as a result of a evenemen. has the objective of identifying and providing information to the community about the validity of the insurance agreement is particularly concerned about a particular case where an object is governed by Article 1320 Book of the Civil Law Act is uncertain, where as the validity of aparticular insurance arrangement agreemen to the object to be definite The research method in this paper uses normative legal research, where to find the ingredients the nassessed using the legislation as well as the use of literature reading. Inconclusion described in the Book of the Law and Commercial Law Number. 2 of 1992 on Insurance Business objects are arranged is certain and clear, With the basics of the insurance agreement is said validin terms of particular agreements.
Keywords: premium, insurance, uncertain object, valid agreement requirements